2013
DOI: 10.1097/jcp.0b013e31828ec934
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Drugs of Abuse and Alcohol Upon Patients Admitted to Acute Psychiatric Wards

Abstract: In acute psychiatric services, rapid and accurate detection of psychoactive substance intake may be required for appropriate diagnosis and intervention. The aim of this study was to investigate the relationship between (a) drug influence as assessed by physicians and (b) blood drug concentrations among patients admitted to acute psychiatric wards. We also explored the possible effects of age, sex, and psychotic symptoms on physician's assessment of drug influence. In a cross-sectional study, the sample compris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
2
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 20 publications
2
2
2
Order By: Relevance
“…Our inclusion rate of 62% compares favorably with other studies on patients admitted to acute psychiatric care (Bagoien et al 2013; Kohigashi et al 2013; Mordal et al 2013). Research on selection bias in recruitment to clinical studies in in-patient psychiatric populations is sparse.…”
Section: Strength and Limitationssupporting
confidence: 79%
“…Our inclusion rate of 62% compares favorably with other studies on patients admitted to acute psychiatric care (Bagoien et al 2013; Kohigashi et al 2013; Mordal et al 2013). Research on selection bias in recruitment to clinical studies in in-patient psychiatric populations is sparse.…”
Section: Strength and Limitationssupporting
confidence: 79%
“…Use of medication with addiction potential was widely under-reported in both sexes, given that 40% of positive toxicology screenings were from patients with no prescriptions for the medications, and many without self-report of recent intake. The prevalence of non-prescribed use of medication with addiction potential has previously been reported to be 15–36% of positive toxicology screenings in acute psychiatry [3, 31]. Our study showed less agreement between self-report of recent substance intake and toxicological screenings in acute psychiatric settings than that earlier reported.…”
Section: Discussioncontrasting
confidence: 90%
“…The present study has limitations. The inclusion rate of 52% is similar to other studies in this setting [ 33 , 34 ]. However, there is a risk of selection bias (i.e.…”
Section: Discussionsupporting
confidence: 85%